2022
DOI: 10.3390/biom12091313
|View full text |Cite
|
Sign up to set email alerts
|

Glycosylation—The Most Diverse Post-Translational Modification

Abstract: This article is part of the Special Issue Glycosylation—The Most Diverse Post-Translational Modification [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Studies have shown that phosphoserine residues can affect secondary protein structures and alter their biological activities and catalytic functions ( Shi, 2009 ). Site 107 of SOD3 is located close to the glycosylation modification site that may play an important role in the modification of translational and post-translational proteins ( Staudacher et al, 2022 ), suggesting that site 107 may alter the antioxidant activity of SOD3. Studies have shown that all SODs require a catalytic metal (Cu or Mn) for their activation ( Fukai and Ushio-Fukai, 2011 ; Skopp et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that phosphoserine residues can affect secondary protein structures and alter their biological activities and catalytic functions ( Shi, 2009 ). Site 107 of SOD3 is located close to the glycosylation modification site that may play an important role in the modification of translational and post-translational proteins ( Staudacher et al, 2022 ), suggesting that site 107 may alter the antioxidant activity of SOD3. Studies have shown that all SODs require a catalytic metal (Cu or Mn) for their activation ( Fukai and Ushio-Fukai, 2011 ; Skopp et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ribavirin) [10] (Figure 1a). N-glycosylation of the carboxamide side chain of glutamine (N-glycan) represents an important mode of posttranslational modification of proteins [11] . However, the distinct chemical properties of various nitrogen motifs, especially their basicity, also pose a significant challenge to the synthesis of N-glycosides [5] .…”
Section: Figure 1 Glycosyl Radical-mediated Synthesis Of N-glycosidesmentioning
confidence: 99%